First record of qualitative losses caused by Meghimatium pictum in vineyards of Southern Brazil and the effects of two molluscicides for its control - Baronio,Cléber Antonio (2014)
This research reports the terrestrial slug Meghimatium pictum (Stoliczka, 1873) (Stylommathophora: Philomycidae) as an agricultural pest for the first time in Southern Brazil vineyards. The species was found in densities exceeding 20 slugs.m-2 in Vitis labrusca L. vineyards at six municipalities of the Southern Brazil's viticulture region. It causes damage a loss by leaving residual mucus on grapes and by consuming grapes already perforated by other organisms, such as insects or birds, or mechanically damaged by in situ compression. The effectiveness of iron phosphate and metaldehyde baits on M. pictum was evaluated in laboratory experiments. Iron phosphate bait was more effective in controlling M. pictum (70%) than metaldehyde bait (15%)